COMPARATIVE ANALYSIS OF ACTUAL AND PREDICTED CANCER MORTALITY IN THE RUSSIAN FEDERATION REGIONS AFFECTED BY RADIOACTIVE CONTAMINATION DUE TO THE CHERNOBYL ACCIDENT - V. V. Kuchumov; A. A. Lyapkalo; M. S. Nikolaevich (Радиационная гигиена, 2015)
Dynamics of the population cancer mortality for the period from 1980 to 1986 as well as for the period from 2004 to 2006 was investigated in 14 regions of the Russian Fed-eration affected by the radioactive contamination due to the Chernobyl accident. Comparison of the indicators with the relevant data from the Orenburg region (control) was done. Mathematic models based on the data from 80-ties were created for the calculation of hypothetic values of mortality indicators in 2004 to 2006. Comparison of actual and predicted values demonstrated that actual morbidity for the urban population was less than the calculated one. Comparison of actual and predicted values of the cancer mortality also demonstrated that for the majority of nozological forms the predicted levels were higher than the actual levels.